Let’s Tajwid Application - Bin Supa'at, Amir Hamzah; SAMAD, ABD (Applied Information Technology And Computer Science, 2023)
The application ‘Let’s Tajwid’ is developed using android studio to solve the problem that faced by some people. People were not initially exposed to the laws of tajwid. There are layers of society that thought they are to old to learn tajwid. After that, some of them feel lazy to learn because they think learn tajwid need a lot of work. This application provided notes about basic tajwid so user can learn through it. This application has voice tutor as well. This application also has questions that will be given to the users. The questions are mostly about what users have learned and user will get marks. The users can set the environment like sound volume and font size on setting menu. The methodology that used during this application development is prototype model. Mostly we used java programming as our program language and Firebase as our database platform.